Environmental and Economic Impact of Support Measures in Agriculture, Albania - Gjermizi, Mirgjana; Tota, Ikbale; Pjetri, Enkeleda; Qerama, Marsela (Richtmann Publishing, 2012)
Agriculture is one of the most important pillars of the economy covering around 52% of the labour force. Recent years thegovernment of Albania is applying support measures in agriculture in order to give support for rural areas and increase the economicsituation of the farmers. The aim of this paper is to find out the environmental and economic impact that the support measures will havein the future for the supported farmers, in their welfare and environment. The scope of these measures is to improve the economic andsocial conditions in rural areas trying to increase the competitiveness and market efficiency, creation of new working possibilities, andincrease the livelihood of the farmers. The study will be done in the basis of the actual situation in the 6 year of the application of thesupport measures, but will be analysed also the needs and opportunities of introducing new measures. It is important to underline thatthis paper will serve to find out the impact in the rural areas of support measures and will be helpful to improve agriculture policies, todefine the most adapted and profitable measures to be applied for the farmers.